2022
DOI: 10.1186/s12888-022-03999-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of working as a peer worker in mental health services: a longitudinal mixed methods study

Abstract: Background Peer workers are increasingly employed in mental health services to use their own experiences of mental distress in supporting others with similar experiences. While evidence is emerging of the benefits of peer support for people using services, the impact on peer workers is less clear. There is a lack of research that takes a longitudinal approach to exploring impact on both employment outcomes for peer workers, and their experiences of working in the peer worker role. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…Recent studies have shown that healthcare workers feeling valued by their organizations had lower odds of experiencing stress, anxiety, and burnout, as well as higher reported engagement at work (Haizlip et al, 2020; Prasad et al, 2021; Teo et al, 2021). Findings from multiple studies have highlighted the importance of developing mutual respect and supportive relationships between peer-support specialists and clinicians in increasing workplace satisfaction (Agarwal et al, 2020; Firmin et al, 2019; Gillard et al, 2022). Although literature on potential interventions is limited, some agencies, such as the City of Philadelphia Department of Behavioral Health and Intellectual Disability Services, have developed training toolkits to better integrate peer staff in the workplace (Philadelphia Department of Behavioral Health and Intellectual Disabilities Services & Achara Consulting, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that healthcare workers feeling valued by their organizations had lower odds of experiencing stress, anxiety, and burnout, as well as higher reported engagement at work (Haizlip et al, 2020; Prasad et al, 2021; Teo et al, 2021). Findings from multiple studies have highlighted the importance of developing mutual respect and supportive relationships between peer-support specialists and clinicians in increasing workplace satisfaction (Agarwal et al, 2020; Firmin et al, 2019; Gillard et al, 2022). Although literature on potential interventions is limited, some agencies, such as the City of Philadelphia Department of Behavioral Health and Intellectual Disability Services, have developed training toolkits to better integrate peer staff in the workplace (Philadelphia Department of Behavioral Health and Intellectual Disabilities Services & Achara Consulting, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a longitudinal, multi-method evaluation study to follow the development and piloting of the peer support intervention between June 2021 and May 2022, drawing on methods used in recent studies of mental health services ( Gillard et al., 2022 ). We collected data from three participant groups: 1) the Core Implementation Team (CIT) were three managers from the student union, the intervention's programme manager, and a university student, 2) peer workers, who were students in the university delivering the intervention, 3) and students at the university (i.e., the client group).…”
Section: Methodsmentioning
confidence: 99%
“…Critical Interpretive Synthesis (CIS) was used to interpret the findings together. CIS has been applied widely to mixed method reviews and other peer support studies ( Gillard et al., 2022 ; McFerran et al., 2016 ). CIS involves tabulating all findings, then developing a set of propositions from these findings through a process of induction.…”
Section: Methodsmentioning
confidence: 99%
“…Nos cuidados de HIV em particular, existem estratégias padronizadas de apoio de pares com base em duas décadas de pesquisa. Na área da saúde mental, por outro lado, temos evidências crescentes dos benefícios do trabalho com pares (Peer Support Workers), indicando uma melhora significativa nos atendidos especialmente na visão de si mesmo, do processo de recuperação e no senso de empoderamento para as pessoas que receberam apoio de pares em comparação com os cuidados habitual (13) .…”
Section: Trabalho Com Pares No Atendimento àS Pessoas Em Situacao De ...unclassified